Perdagangan Elektronik: Suatu Bentuk Pasar Baru yang Menjanjikan? - Purnastuti, Losina (Jurnal Ekonomi dan Pendidikan, 2012)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->Electronic Commerce is claimed as a form of new market in electronic era. Although most current use of Electronic Commerce occurs at the inter-corporate and inter-organizational levels, Electronic Commerce services aimed at individual consumers are developing rapidly. The internet is a major catalyst in the diffusion of Electronic commerce into an increasing number of economic spheres, and is rapidly harmonizing the general environment in which electronic transactions of all kinds take place. This form of new market is able to create some incentives both in transaction management and business efficiency area. On the other hand, implementation of Electronic Commerce become an issue discussed extensively from many of point of view including: law, economic and technology.